CD19+ CD24hi CD38hi Regulatory B Cells and Memory B Cells in Periodontitis: Association with Pro-Inflammatory and Anti-Inflammatory Cytokines - Helal F. Hetta; Ibrahim M. Mwafey; Gaber El-Saber Batiha; Suliman Y. Alomar; Nahed A. Mohamed; Maggie A. Ibrahim; Abeer Elkady; Ahmed Kh. Meshaal; Hani Alrefai; Dina M. Khodeer; Asmaa M. Zahran (Vaccines, 2020)
Regulatory B cells (Bregs) are unique subpopulations of B cells with immune-regulating or immune-suppressing properties and play a role in peripheral tolerance. Due to the current limitations of human Breg studies among periodontal diseases, in the present study, we tried to analyze the change in circulating Bregs, pro-inflammatory, and anti-inflammatory cytokines in patients with periodontitis. Peripheral blood from 55 patients with stage 2 periodontitis and 20 healthy controls was analyzed using flow cytometry to evaluate the frequency of CD19+CD24+CD38+ Breg cells. ELISA was used to assess the serum levels of the pro-inflammatory cytokines, including interleukins (IL)-1β, IL-6, TNF-α, and anti-inflammatory cytokines including IL-10, IL-35, and TGF-β. Increased proportions of Breg cells were observed in patients with stage 2 periodontitis compared to controls. Serum levels of cytokines were significantly higher in patients with periodontitis compared to controls. A significant positive correlation was observed between the frequencies of Breg cells and IL35 levels, IL10 levels, and TGF-β. In conclusion, our results suggest that the increase in peripheral Breg cells and serum cytokine levels among periodontitis patients seems to be closely associated with disease progression, a possible link between periodontitis, and systemic inflammatory process.